Simple, concise, stereocontrolled synthesis of (8E,10Z)-pentadecadien-1-ol acetate - Chavan, Subhash P.; Kharul, Rajendra K.; Kamat, Subhash K.; Kalkote, Uttam R.; Kale, R. R. (Synthetic Communications, 2005)
A simple, concise, and stereocontrolled synthesis of (8E, 10Z)-pentadecadien-l -ol acetate involving a Cadiot-Chodkiewicz reaction as the key step is described.
Keywords: acetate; Acrobasis vaccini; Cadiot-Chodkiewicz reaction; diacetylene; Pheromone

Short and efficient synthesis of rubrolide E - Chavan, Subhash P.; Pathak, Ashok B.; Pandey, Ankur; Kalkote, Uttam R. (Synthetic Communications, 2007)
Short and efficient synthesis of rubrolide E from commercially available 4-methoxyacetophenone, employing ring-closing metathesis, Knoevenagel condensation, and Reformatsky reactions, are the key steps are described.
Keywords: antibiotics; antitumor; Epoxide; Natural products; Total synthesis

Studies toward the total synthesis of carba analogue of motif C OF M. TB cell wall AG complex - Gurjar, Mukund K.; Reddy, Challa Nageswar; Kalkote, Uttam R.; Chorghade, Mukund S. (Heterocycles, 2009)
Herein we describe the synthesis of the carba analogue of motif C of arabinogalactan complex present in M tuberculosis cell wall. Pd(0) catalyzed allylic alkylation and Fraser-Reid's glycosidation are the two key reactions that were employed for the synthesis of central glycosyl accepter unit and the glycosylation respectively.
Keywords: Allylic Alkylation; desymmetrization; Fraser-Reid's Glycosidation; M. Tb Ag Complex; Mycobacterium tuberculosis